2007
DOI: 10.1002/ab.20190
|View full text |Cite
|
Sign up to set email alerts
|

A latent variable modeling approach to identifying subtypes of serious and violent female juvenile offenders

Abstract: Females have recently become an important population in research related to serious and violent juvenile offending. Although a small body of research exists on girls in the deep end of the system, very few studies have examined the degree of heterogeneity within high-risk female samples. This study applied latent class analysis (LCA) to identify subgroups of female juvenile offenders based on their self-report of offending profiles (N=133). Results supported a three-class solution with subgroups characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
107
0
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 59 publications
12
107
0
6
Order By: Relevance
“…On-going debate between perspectives underscores the need for more investigation of gender differences in offending (Fitzgerald et al, 2012). Further trends in offending such as rising rates of violent crime amongst women, add to the impetus to explore differences between and within gender groups (Odgers et al, 2007;Fitzgerald et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On-going debate between perspectives underscores the need for more investigation of gender differences in offending (Fitzgerald et al, 2012). Further trends in offending such as rising rates of violent crime amongst women, add to the impetus to explore differences between and within gender groups (Odgers et al, 2007;Fitzgerald et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nock et al (2006) concluded that the best fitting model included six ranked latent classes ranging from no conduct disorder to pervasive conduct disorder. A similar pattern was reported by Eaves et al (1993) and Odgers et al (2007). In short, each of these studies involved fitting latent class models to externalizing behaviors, but the classes that emerged seemed to represent degrees of severity on an underlying continuum.…”
Section: Discussionmentioning
confidence: 83%
“…Although latent class analyses of adolescent externalizing behaviors involve a different model (Brownfield and Sorsenson 1987;Eaves et al 1993;Nock et al 2006;Odgers et al 2007), findings from latent class research can be reconciled with ours. In each of the latent class analyses reported to date, the classes that emerged were graded in terms of severity, as opposed to being distinct in a nominal sense (i.e., classes where probabilities of item endorsement did not increase monotonically across classes but were instead unique in each class).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Giancola et al (2009) experimentally assessed the effects of alcohol on aggression in both males and females, finding aggression increased for both sexes after alcohol, but that this increase was more apparent in males. However, research into adolescents does show increasing rates of violence among females too (Odgers et al, 2007), and Graves (2007) concludes that gender differences in serious violent acts are fading. Research employing a large student sample identified a particular problem of increased risk taking when intoxicated, and that these risks covered a variety of domains e.g.…”
Section: Introductionmentioning
confidence: 99%